Use of testicular sperm for intracytoplasmic sperm injection in men with high sperm DNA fragmentation: a SWOT analysis - Sandro C Esteves; Matheus Roque; Nicolás Garrido (Asian Journal of Andrology, 2018)
Spermatozoa retrieved from the testis of men with high levels of sperm DNA fragmentation (SDF) in the neat semen tend to have better DNA quality. Given the negative impact of SDF on the outcomes of Assisted Reproductive Technology (ART), an increased interest has emerged about the use of testicular sperm for intracytoplasmic sperm injection (Testi-ICSI). In this article, we used a SWOT (strengths, weaknesses, opportunities, and threats) analysis to summarize the advantages and drawbacks of this intervention. The rationale of Testi-ICSI is bypass posttesticular DNA fragmentation caused by oxidative stress during sperm transit through the epididymis. Hence, oocyte fertilization by genomically intact testicular spermatozoa may be optimized, thus increasing the chances of creating a normal embryonic genome and the likelihood of achieving a live birth, as recently demonstrated in men with high SDF. However, there is still limited evidence as regards the clinical efficacy of Testi-ICSI, thus creating opportunities for further confirmatory clinical research as well as investigation of Testi-ICSI in clinical scenarios other than high SDF. Furthermore, Testi-ICSI can be compared to other laboratory preparation methods for deselecting sperm with damaged DNA. At present, the available literature supports the use of testicular sperm when performing ICSI in infertile couples whose male partners have posttesticular SDF. Due to inherent risks of sperm retrieval, Testi-ICSI should be offered when less invasive treatments for alleviating DNA damage have failed. A call for continuous monitoring is nonetheless required concerning the health of generated offspring and the potential complications of sperm retrieval.